Hierarchy model of Tambak Lorok slum area transformation to support marine tourism kampong. (November 2018) - Sunarti,; Rahdriawan, M; Dewi, A P; Widiarta, J R
Abstract: Tambak Lorok is a fishermen residential area in Semarang which is declared as slums in Mayor regulation No.050/801/2014. Tambak Lorok is now a national development priority as Marine Tourism Kampong. Government has provided several environmental improvement programs but settlements still in slum condition. Research aim is to study the Tambak Lorok settlement transformation in supporting the development of Marine Tourism Kampong. Research method used is mix method. The results obtained that the transformation that occurred is a partial transformation that is only on the infrastructure to support the development of Marine Tourism Kampong.